Cellular Kinetics of Perivascular MSC Precursors. (18th August 2013) - Chen, William C. W.; Park, Tea Soon; Murray, Iain R.; Zimmerlin, Ludovic; Lazzari, Lorenza; Huard, Johnny; Péault, Bruno
Abstract : Mesenchymal stem/stromal cells (MSCs) and MSC-like multipotent stem/progenitor cells have been widely investigated for regenerative medicine and deemed promising in clinical applications. In order to further improve MSC-based stem cell therapeutics, it is important to understand the cellular kinetics and functional roles of MSCs in the dynamic regenerative processes. However, due to the heterogeneous nature of typical MSC cultures, their native identity and anatomical localization in the body have remained unclear, making it difficult to decipher the existence of distinct cell subsets within the MSC entity. Recent studies have shown that several blood-vessel-derived precursor cell populations, purified by flow cytometry from multiple human organs, give rise to bona fide MSCs, suggesting that the vasculature serves as a systemic reservoir of MSC-like stem/progenitor cells. Using individually purified MSC-like precursor cell subsets, we and other researchers have been able to investigate the differential phenotypes and regenerative capacities of these contributing cellular constituents in the MSC pool. In this review, we will discuss the identification and characterization of perivascular MSC precursors, including pericytes and adventitial cells, and focus on their cellular kinetics: cell adhesion, migration, engraftment, homing, and intercellular cross-talk during tissue repair and regeneration.